2023
DOI: 10.11591/eei.v12i1.4385
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of tomato viral leaf diseases detection using machine learning classification techniques

Abstract: Agriculture is the backbone of India and more than 50% of the population is dependent on it. With the increasing demand for food with the increase in population, it is the need of time that crops should be prevented against diseases. More than 1K acres of land with tomato diseases got affected in Pune only during this pandemic (2021). It could have been prevented by correct identification of the disease and then by corrective measures. This paper presents the experimental and comparative study of tomato leaf d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Also covered were biotic illnesses brought on by bacterial and fungal infections, specifically tomato leaf blight, blast, and browning. The precision of the recommended model's identification rate is 98.49% [9]. The recommended model was evaluated against variants of visual geometry group (VGG) and ResNet with the identical dataset.…”
Section: Methodsmentioning
confidence: 99%
“…Also covered were biotic illnesses brought on by bacterial and fungal infections, specifically tomato leaf blight, blast, and browning. The precision of the recommended model's identification rate is 98.49% [9]. The recommended model was evaluated against variants of visual geometry group (VGG) and ResNet with the identical dataset.…”
Section: Methodsmentioning
confidence: 99%
“…The model is trained on a dataset of 8,000 photos and achieves an accuracy of 92.6% by utilizing CNN for feature extraction and SVM for classification. [18] presents an experimental study comparing traditional ML algorithms (RF, SVM, NB) with a deep learning CNN algorithm in order to classify tomato leaf disease. The results show that the CNN approach outperforms traditional methods, achieving over 95% accuracy in detection and classification.…”
Section: Related Workmentioning
confidence: 99%
“…In addtional, approach of study, utilizing the ResNet-50 model, delivered a remarkable outcome, achieving a substantial accuracy rate of 96.35% when tested on a balanced dataset split, with 50% used for training and the remaining 50% for testing. In this study [25], Sanjeela Sagar and Jaswinder Singh conducted an experimental and comparative analysis of tomato leaf disease classification, employing both traditional machine learning algorithms such as random forest (RF), support vector machines (SVM), and naïve bayes (NB), as well as a deep learning convolutional neural network (CNN) algorithm. Notably, our findings revealed that the CNN, specifically when integrated with a pre-trained Inception v3 model, outperformed traditional methods.…”
Section: Related Workmentioning
confidence: 99%